Synthetic antitumor vaccines containing MUC1 glycopeptides with two immunodominant domains: induction of a strong immune response against breast tumor tissues - Gaidzik, Nikola; Kaiser, Anton; Kowalczyk, Danuta; Westerlind, Ulrika; Gerlitzki, Bastian; Sinn, Peter; Schmitt, Edgar; Kunz, Horst (Angewandte Chemie. International edition, 2011)
A shot in the arm for cancer treatment: Two MUC1 tetanus toxoid vaccines were synthesized and induced a strong immune response in mice. The antibodies elicited by the vaccines show a high selectivity for the tumor cells in mammary carcinoma tissues and also distinguish between tumor tissues at different stages.
Gesehen am 12.07.2023